The processing of conversion in English : morphological complexity and underspecification - Darby, J (2015)
This thesis investigates a subset of the lexical items which appear to be involved in the phenomenon of conversion in English. In its most canonical form, conversion involves pairs or sets of word forms which share both their phonological (and orthographic) form as well as some element of meaning, but which seem to belong to di↵erent word classes. In this study, the focus is on the relationships (or lack thereof) between monosyllabic verbal and nominal forms in conversion pairs. The investigation takes as a starting point the patterns of linguistic behaviour within and across these pairs. The situation which is revealed is complex, but not unsystematic. Instead, it is shown that in many cases, the relationship between the nominal and verbal forms is clearly asymmetrical. In contrast to these clearer patterns, however, there are also a number of cases wherein the relationship appears to be more symmetrical in nature. In view of the complexity of the situation, the question of how to best model the linguistic behaviour of such forms has been a subject of some debate in the literature. A variety of theoretical explanations for these relationships have been proposed, though none has managed to account for the wide range of data. This study therefore suggests a mixed model, in which asymmetrically-related forms are involved in a derivational morphological process, while symmetrical forms represent inflected forms of a single lexeme which lacks a specification of word class. However, given the fertile – and in no way settled – research background, the primary contribution of this study is an experimental exploration of how these forms and the relationships between them might be synchronically represented in the mental grammar of current speakers. To that end, three behavioural experiments are conducted with a view to uncovering how di↵erent types of conversion items are processed, and how information about their processing might inform our theoretical understanding. The results of these experiments suggest that the processing of these forms is indeed in line with the patterns of symmetry and asymmetry found in their linguistic behaviour, and suggests that some conversion pairs may be involved in a derivational process, while others may not be pairs at all but rather a single, underspecified lexical entry. However, in addition to the results concerning the forms which display clearer patterns of behaviour, it is suggested that the patterns across the phenomenon of conversion as a whole may best be understood as a continuum, rather than all suggesting a single underlying pattern of mental representation.